Clinical toxicology : principles and mechanisms - Barile, Frank A. (New York : Informa Healthcare, 2010)
Examining the complex interactions associated with clinical toxicological events and chemical exposure of drug administration, this updated and revised Second Edition functions as a stand-alone text or reference of clinical toxicology for professionals, students of toxicology and pharmacy, as well as forensic toxicologists, occupational healthcare workers, industrial hygienists, and safety engineers. This all-inclusive source has been updated to include the latest issues and the most current research in clinical toxicology.
pt. 1. Introduction to basic toxicological principles -- pt. 2. Toxicity of therapeutic agents -- pt. 3. Toxicity of non-therapeutic agents.
Includes bibliographical references and index.
Keywords: CLINICAL TOXICOLOGY